Analysis of Academic Supervision in Distance Learning During the Covid 19 Pandemic - Permatasari, Amelia; Lian, Bukman; Putra, Alhadi Yan (Yayasan Sembilan Pemuda Indonesia, 2022)
The purpose of this research is to identify and analyze: (1) distant learning at MAN 1 Muara Enim, and (2) academic supervision of remote learning during the covid-19 epidemic. This research employs qualitative methods with a descriptive approach. The study was conducted at MAN 1 Muara Enim, with data collected through observation, interviews, documentation, and a literature review with 64 instructors, two principals, and one Madrasah supervisor. The findings revealed that MAN 1 Muara Enim completed a series of good preparations, the academic supervision approach, which is typically done face-to-face, is now done remotely and is divided into two parts, manually verifying the lesson plan and synchronizing the online learning. This study contributes to the topic of Education Management, specifically academic supervision in sustaining teacher performance sustainability.